"It's okay even if you are a spy": issues in researcher positioning within a precarious workplace. Issue 1 (19th December 2019) - Baum-Talmor, Polina
Abstract : Purpose: The purpose of this paper is to examine some of the complexities associated with the trust-building process between participants and researcher in the context of a precarious work environment. Specifically, the paper seeks to discuss issues arising from the power dynamics, mistrust and tensions between different stakeholders in the research (i.e. employers, employees and the researcher), and the implications of such relationships for establishing rapport and trust with research participants. Design/methodology/approach: This paper uses the case of the shipping industry and is based upon findings from two research projects. One project examined similarities and differences between the merchant vessel and Goffman's theoretical conceptualisation of "total institutions" (Goffman, 1961 ); the other focused on the increasing flexibility of labour in the global labour market, using the case of shipping. Both projects incorporated ethnographic research methods which included three voyages on board merchant vessels, as well as interviews and informal conversations with over 100 participants. Findings: The researcher encountered several obstacles throughout the projects, many of which related to the access to the restricted workplace setting of a cargo ship. However, this paper is based on her positioning in the field after permission to access the ship had been granted by the shipping company. It was often challenging to overcome participants' suspicions of the researcher as being sent by the company to spy on them. The researcher generally managed to overcome such suspicions in the course of her fieldwork by building relationships with participants over time. Nevertheless, these relationships were influenced by the complex power dynamics amongst the different stakeholders in the field. The challenges encountered in the field sites suggest that researchers should be open and fluid in the ways they present themselves in the field. The findings potentially offer useful insights for novice researchers whose research focuses on workplace settings characterised by precariousness of employment and for those conducting shipboard research. Originality/value: The main contribution of this paper lies within its ability to shed light on the often-delicate relationships between different stakeholders in a research project, and the influence of these relationships on a researcher's continuous access to the field. The experiences described in this paper are based on the global shipping industry, but they are also relevant to other closed, isolated and/or restricted research settings. Specifically, experiences described in this paper are similar to those of researchers studying "closed" research environments that are not accessible to the general public; this is particularly the case where a hierarchical work structure controls to some extent the roles played by different stakeholders within the precarious work environment, potentially influencing the way someone from outside the workplace approaches it. These include, for example, government owned establishments such as prisons, mental hospitals as well as privately owned closed business organisations.